The illusion of explanatory depth and endorsement of conspiracy beliefs. (15th June 2018) - Vitriol, Joseph A.; Marsh, Jessecae K.
Abstract: The average person possesses superficial understanding of complex causal relations and, consequently, tends to overestimate the quality and depth of their explanatory knowledge. In this study, we examined the role of this illusion of explanatory depth (IOED) in politics—inflated confidence in one's causal understanding of political phenomena—for endorsement of conspiracy beliefs. Utilizing a pre‐/post‐election panel design and a large sample of U.S. Citizens ( N = 394) recruited in the context of the 2016 presidential election, we provide evidence that political IOED, but not a non‐political IOED, was associated with increased support for general and election‐specific conspiracy beliefs, particularly among political novices and supporters of the losing candidate. We find this pattern of results net the influence of a broad range of variables known to covary with conspiracy beliefs. Implications for theory and the need for future research are discussed.